Clinical Evaluation of Mother Tincture as an Antihypertensive - Kurian John Poruthukaren MD; Princy L. Palatty MD; Manjeshwar S. Baliga PhD; Sucharita Suresh MSc (SAGE Publishing, 2014)
Viscum album , an infrequently used antihypertensive in homeopathy, is evaluated by 1-group pretest-posttest model in primary hypertension. The drug was administered for 12 weeks at a dosage of 10 drops 3 times a day. Using paired t test, a significant drop in blood pressure ( P < .0001) and serum triglyceride ( P < .0001) was observed in the treatment group. This dual effect of Viscum album shows promise in optimizing therapy for primary hypertension.